1975
DOI: 10.1037/h0076605
|View full text |Cite
|
Sign up to set email alerts
|

Benefit-cost analysis of a token economy program.

Abstract: Benefit-Cost Analysis of a Token Economy ProgramA benefit-cost analysis of a token economy program with adult psychiatric patients examined the hospital costs foregone by getting and keeping patients out of the hospital, minus the extra costs to the public incurred by the patients once they had been released.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1976
1976
1985
1985

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…For example, the expense (cost) of token economies has been examined in different ways. Operating costs, cost-effectiveness, and cost-benefit analyses have shown that major benefits accrue from adopting token economies in relation to existing alternatives such as routine psychiatric care or detention centers for juvenile offenders (e.g., Foreyt, Rockwood, Davis, Desvousges, & Hollingsworth, 1975;Kirigin et al, 1979;Paul & Lentz, 1977).…”
Section: Dissemination Of the Token Economymentioning
confidence: 99%
“…For example, the expense (cost) of token economies has been examined in different ways. Operating costs, cost-effectiveness, and cost-benefit analyses have shown that major benefits accrue from adopting token economies in relation to existing alternatives such as routine psychiatric care or detention centers for juvenile offenders (e.g., Foreyt, Rockwood, Davis, Desvousges, & Hollingsworth, 1975;Kirigin et al, 1979;Paul & Lentz, 1977).…”
Section: Dissemination Of the Token Economymentioning
confidence: 99%
“…The cost-benefit ratio was determined by a Present Value analysis (Foreyt, et al, 1975). Thus for each dollar spent on the behavioral treatment program (in addition to the cost of providing custodial care), the Present Value analysis calculates the ~ount which would need to be invested at the present time, in order to provide care for those patients had there been no treatment program.…”
Section: Program Costs and Feasibility With The Elderlymentioning
confidence: 99%